Type 2 diabetes presenting with hyperglycaemic hyperosmolar state in an adolescent renal transplant patient - Harrington, Francesca Ruth (BMJ Case Rep, 2015)
Hyperglycaemic hyperosmolar state (HHS) is a life-threatening condition rarely seen in paediatrics. It is becoming increasingly recognised with the growing incidence of childhood type 2 diabetes mellitus (T2DM). We present a 16-year-old boy with Bardet-Biedl syndrome, with comorbidities including chronic renal impairment requiring renal transplant, isolated growth hormone (GH) deficiency and obesity, who presented on routine follow-up with new onset T2DM and in HHS. Investigations revealed hyperglycaemia (45.7 mmol/L), ketones of 0.1 mmol/L, pH 7.38 and osmolarity 311 mOsmol/kg. After acute management with fluid resuscitation and intravenous insulin, he is now stable on metformin. He has lost weight, renal function is stable and he has stopped GH therapy. We discuss the dilemmas encountered in his long-term management due to his renal transplant and comorbidities, and whether or not, given his significant T2DM risk, this case was preventable or predictable.